Effect of Dietary Crude Protein and Apparent Metabolizable Energy Levels on Growth Performance, Nitrogen Utilization, Serum Parameter, Protein Synthesis, and Amino Acid Metabolism of 1- to 10-Day-Old Male Broilers - Yu, Yao; Ai, Chunxiao; Luo, Caiwei; Yuan, Jianmin (International journal of molecular sciences, 2024)
This research compared how different levels of dietary crude protein (CP) and apparent metabolizable energy (AME) affect the growth performance, nitrogen utilization, serum parameters, protein synthesis, and amino acid (AA) metabolism in broilers aged 1 to 10 days. In a 4 × 3 factorial experimental design, the broilers were fed four levels of dietary CP (20%, 21%, 22%, and 23%) and three levels of dietary AME (2800 kcal/kg, 2900 kcal/kg, and 3000 kcal/kg). A total of 936 one-day-old male Arbor Acres broilers were randomly allocated to 12 treatments with 6 replications each. Growth performance, nitrogen utilization, serum parameter, gene expression of protein synthesis, and AA metabolism were evaluated at 10 d. The results revealed no interaction between dietary CP and AME levels on growth performance (p > 0.05). However, 22% and 23% CP enhanced body weight gain (BWG), the feed conversion ratio (FCR), total CP intake, and body protein deposition but had a detrimental effect on the protein efficiency ratio (PER) compared to 20% or 21% CP (p < 0.05). Broilers fed diets with 2800 kcal/kg AME showed increased feed intake (FI) and inferior PER (p < 0.05). Broilers fed diets with 3000 kcal/kg AME showed decreased muscle mRNA expression of mammalian target of the rapamycin (mTOR) and Atrogin-1 compared to those fed diets with 2800 kcal/kg and 2900 kcal/kg AME (p < 0.05). Increasing dietary CP level from 20% to 23% decreased muscle mTOR and increased S6K1 mRNA expression, respectively (p < 0.05). The muscle mRNA expression of Atrogin-1 was highest for broilers fed 23% CP diets (p < 0.05). The mRNA expression of betaine homocysteine methyltransferase (BHMT) and Liver alanine aminotransferase of the 22% and 23% CP groups were higher than those of 20% CP (p < 0.05). Significant interactions between dietary CP and AME levels were observed for muscle AMPK and liver lysine-ketoglutarate reductase (LKR) and branched-chain alpha-keto acid dehydrogenase (BCKDH) mRNA expression (p < 0.05). Dietary AME level had no effect on muscle AMPK mRNA expression for broilers fed 21% and 22% CP diets (p > 0.05), whereas increasing dietary AME levels decreased AMPK mRNA expression for broilers fed 23% CP diets (p < 0.05). The mRNA expression of LKR and BCKDH was highest for broilers fed the diet with 2800 kcal/kg AME and 22% CP, while it was lowest for broilers fed the diet with 3000 kcal/kg AME and 20% CP. The findings suggest that inadequate energy density hindered AA utilization for protein synthesis, leading to increased AA catabolism for broilers aged 1 to 10 days, and a dietary CP level of 22% and an AME level of 2900 to 3000 kcal/kg may be recommended based on performance and dietary protein utilization.